Low carbohydrate diet: are concerns with saturated fat, lipids, and cardiovascular disease risk justified?. Issue 5 (October 2020) - Diamond, David M.; O'Neill, Blair J.; Volek, Jeff S.
Abstract : Purpose of review: There is an extensive literature on the efficacy of the low carbohydrate diet (LCD) for weight loss, and in the improvement of markers of the insulin-resistant phenotype, including a reduction in inflammation, atherogenic dyslipidemia, hypertension, and hyperglycemia. However, critics have expressed concerns that the LCD promotes unrestricted consumption of saturated fat, which may increase low-density lipoprotein (LDL-C) levels. In theory, the diet-induced increase in LDL-C increases the risk of cardiovascular disease (CVD). The present review provides an assessment of concerns with the LCD, which have focused almost entirely on LDL-C, a poor marker of CVD risk. We discuss how critics of the LCD have ignored the literature demonstrating that the LCD improves the most reliable CVD risk factors. Recent findings: Multiple longitudinal clinical trials in recent years have extended the duration of observations on the safety and effectiveness of the LCD to 2–3 years, and in one study on epileptics, for 10 years. Summary: The present review integrates a historical perspective on the LCD with a critical assessment of the persistent concerns that consumption of saturated fat, in the context of an LCD, will increase risk for CVD.